Participatory development communication as a pattern of community empowerment (Study on the Radio of the An-Nur Malang Islamic Dakwah Community) - Maulidiana, Fina Maysaroh Nur; Sujoko, Anang; Prasetyo, Bambang Dwi (Technium Social Sciences Journal, 2021)
This research aims to determine the patterns and management system used at Radio Dakwah Islamiyah to empower members of the community. One of the methods used in this study is to examine the participatory development communication patterns that are commonly used to find out the participation of community members to carry out development in Radio Dakwah Islamiyah An-Nur Malang. This study used qualitative methods and the techniques to collecting the data using in-depth interviews with An-Nur foundation as the founder in operating the establishment of An-Nur Da'wah Islamiyah Radio, as well as community members on the radio. The informants of this research consisted of : the chairman of An-Nur Foundation, the Chairperson of An-Nur's Da'wah Islamiyah Radio, the creative team and secretary of An-Nur Da'wah Islamiyah Radio. From some of the informants, the methods used by Radio Dakwah Islamiyah An-Nur Malang will be examined in an effort to empower community members and the management used to maintain their existence. The result of this study, participatory development communication are already used in managing Radio Dakwah Islamiyah An-Nur to increase their exist. One of the method used is collecting the donation from community members and it is work. The income totally used to establish the Islamic dakwah through radio media.